2013
DOI: 10.1038/bmt.2013.145
|View full text |Cite
|
Sign up to set email alerts
|

Etoposide-containing conditioning regimen reduces the occurrence of hemophagocytic lymphohistiocytosis after SCT

Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a rare life-threatening disease of severe hyperinflammation caused by uncontrolled proliferation of activated lymphocytes and macrophages that secrete high amounts of inflammatory cytokines. HLH occurring after SCT is difficult to diagnose. It is characterized by severe clinical manifestations and high mortality. Despite current therapeutic approaches, outcomes remain poor. We analyzed the incidence and risk factors of HLH after SCT and the response to treatment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 20 publications
(41 reference statements)
3
24
0
Order By: Relevance
“…The reported incidence of secondary HLH after HSCT for malignancies in adults ranges from 4% to 17% in the first 9 months. [24][25][26][27] To account for this uncertainty, we separately analyzed HLH events that occurred during and events that occurred after the phase of most profound immune suppression, with a cutoff at 180 days after HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of secondary HLH after HSCT for malignancies in adults ranges from 4% to 17% in the first 9 months. [24][25][26][27] To account for this uncertainty, we separately analyzed HLH events that occurred during and events that occurred after the phase of most profound immune suppression, with a cutoff at 180 days after HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…There seems to be a disproportionately higher incidence of HLH after allogeneic as compared to autologous HSCT as shown by Abdelkefi et al (8.8% in allogeneic vs 0.9% in autologous HSCT group). Kobayashi et al showed a similar trend but a large multicenter study from Europe by Redjoul et al reported a much lower incidence of 0.3%. Furthermore, patients receiving UCB graft (especially those with a higher degree of HLA mismatch; 4/6) or those undergoing haploidentical PBSC transplantation with post‐transplant Cy have a significantly higher risk for post‐HSCT HLH .…”
Section: Discussionmentioning
confidence: 71%
“…Other factors associated with significant risk of post‐HSCT HLH include fewer CD34+ cells (<7.66 × 10 4 /kg of recipient weight) in the UCB graft as shown by Takagi et al and SAA as shown by Abdelkefi et al. However, other studies have not revealed similar associations . Interestingly, Kobayashi et al reported that VP‐16, an integral part of the current therapeutic protocol for HLH, when used in conditioning regimen is associated with significantly lower frequency of post‐HSCT HLH.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations